An inverse problem resolution via piecewise linear underestimation (Publicaciones en Ciencias y Tecnología, 2012)
In reactor design phase bubble column type (CBT) is required to have the distribution of solids within the reactor. This distribution satisfies an ordinary diferential equation (ODE) of order two, with boundary conditions that was developed by D. R. Cova, followed by D. N. Smith and J. A. Ruether. Some elements of this equation are given by correlations that depend on certain parameters that are unknown but may be obtained from experimental data. The methodology used to determine these parameters is the subpiecewise linear underestimation developed by O. L. Mangasarian, J. B. Rosen, M. E. Thompson.
Keywords: Inverse problems; global optimization; piecewise linear underestimation; linear programming